Practical estuarine chemistry: handbook - Head P C (London Cambridge University Press, 1985)
Originally published in 1985, this is the second of a series of handbooks sponsored by the Esturaine and Brackish-Water Sciences association. The book concentrates on the techniques and practicalities of data collection from the estuarine environment. It is intended that the information presented will increase the reader's understanding of estuarine processes thus enabling him to devise sensible sampling programmes and to interpret the results once obtained. Techniques discussed include trace element and organic matter analysis, use of ion-selective electrodes, and measurement of salinity, dissolved oxygen and nutrients. The text will be of primary relevance for aquatic chemists, but should also be of use to biologists, physicists, geologists and oceanographers working in estuaries.
Keywords: Surface features of the earth